Gastric Trichobezoar with Outlet Obstruction in a Child of 4 Years old - A Rare Occurrence - Naher, Begum Sharifun; Kawser, Chowdhury Ali; Amin, Ruhul; Ishaq, SM (Bangladesh Journal of Child Health, 2010)
DOI: 10.3329/bjch.v34i1.5699 Bangladesh Journal of Child Health 2010; Vol.34(1): 25-27